(untitled) (Journal of International Crisis and Risk Communication Research, 2021)
The COVID-19 pandemic started in December 2019 and has rapidly spread around the globe. Among the institutions at the forefront of responding to COVID-19 are U.S. colleges and universities. These institutions frequently face crises, but they have not always managed these episodes successfully. Given the gravity of the pandemic, best practices research can help higher education institutions combat public health crises and other threats. This study examines and assesses the crisis communication of U.S. colleges and universities in response to the COVID-19 pandemic using the best practices framework. Findings indicate that higher education institutions have employed communication consistent with best practices, with some important modifications. Findings also answer calls to contextualize crisis communication best practices within specific organizational contexts and as a values-based framework.